Dietary Patterns, Weight Perception and Obesity Status, among 10-12-Year-Old Children; an Epidemiological Study in Greece - Aikaterini Kanellopoulou; Rena I. Kosti; Venetia Notara; George Antonogeorgos; Andrea Paola Rojas-Gil; Ekaterina N. Kornilaki; Areti Lagiou; Mary Yannakoulia; Demosthenes B. Panagiotakos (MDPI AG, 2021)
Adherence to certain dietary patterns influences obesity status in both children and adults. Weight perception influences dietary habits. The aim of this study was to examine children's dietary habits and obesity status, in relation to weight perception. One thousand seven hundred Greek students enrolled in this study during 2014-2016. Children's characteristics were assessed through validated questionnaires, and weight status was classified according to the criteria of the International Obesity Task Force. Dietary patterns were assessed through exploratory factor analysis. Overall, 52.2% of children characterized themselves as normal weight, 34.5% as low weight, and 13.3% as overweight/obese; 52.5% of children were in accordance with their actual weight status, with girls being more likely to overestimate their weight. Children followed three dietary patterns, i.e., starchy and protein foods, unhealthy/high-fat foods, and healthy foods. Children who followed the healthy dietary pattern and had accurate weight perception (in accordance with their actual weight), had lower odds of being overweight/obese (p < 0.001). Accurate weight perception in conjunction with healthy dietary habits may play a determinant role in the prevention of obesity. From a public health perspective, early identification of children's weight misperception along with healthy dietary habit promotion shape a crucial role in childhood obesity confrontation.